2017
DOI: 10.1053/j.gastro.2016.09.033
|View full text |Cite
|
Sign up to set email alerts
|

Infection of Hepatocytes With HCV Increases Cell Surface Levels of Heparan Sulfate Proteoglycans, Uptake of Cholesterol and Lipoprotein, and Virus Entry by Up-regulating SMAD6 and SMAD7

Abstract: BACKGROUND & AIMS The signaling molecule and transcriptional regulator SMAD6, which inhibits the transforming growth factor beta (TGFB) signaling pathway, is required for infection of hepatocytes by hepatitis C virus (HCV). We investigated the mechanisms by which SMAD6, and another inhibitory SMAD (SMAD7), promote HCV infection in human hepatoma cells and hepatocytes. METHODS We infected Huh7 and Huh7.5.1 cells and primary human hepatocytes with JFH1 HCVcc; we measured HCV binding, intracellular levels of HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 54 publications
1
46
0
Order By: Relevance
“…This agrees with the increased levels of BMP-6 expression observed after JUNV infection in OBCs. Similarly, upregulation of BMPs/Smad signaling pathway has been reported as necessary for viral entry in the case of infection of hepatocytes with hepatitis C virus [26]. In the case of human hepatitis B virus and human immunodeficiency virus, it has been described that an increase in viral transcription and replication is mediated by transforming growth factor-β/BMP signaling, iron or hepcidin either in human hepatocytes or human primary macrophages, and CD4+ T cells, respectively [27, 28].…”
Section: Discussionmentioning
confidence: 99%
“…This agrees with the increased levels of BMP-6 expression observed after JUNV infection in OBCs. Similarly, upregulation of BMPs/Smad signaling pathway has been reported as necessary for viral entry in the case of infection of hepatocytes with hepatitis C virus [26]. In the case of human hepatitis B virus and human immunodeficiency virus, it has been described that an increase in viral transcription and replication is mediated by transforming growth factor-β/BMP signaling, iron or hepcidin either in human hepatocytes or human primary macrophages, and CD4+ T cells, respectively [27, 28].…”
Section: Discussionmentioning
confidence: 99%
“…5 Transcriptomics analysis revealed that silencing of SMAD6 decreased the expression of HSPGs, with a corresponding reduction in cell surface expression of heparan sulfate. 3 Furthermore, SMAD6 knockdown decreased expression of cholesterol uptake receptors and HCV entry factors, including low-density lipoprotein receptor and scavenger receptor class B1 type I. In contrast, exogenous expression of SMAD6 was shown to up-regulate the expression of HSPGs and cholesterol uptake receptors.…”
mentioning
confidence: 96%
“…Furthermore, a comprehensive identification of HCV host dependencies is crucial to better understand the pathogenesis of HCV-induced liver disease biology and to identify strategies for the prevention of hepatocellular carcinoma. In this issue of Gastroenterology , Zhang et al 3 characterize the role of SMAD6 in the regulation of HCV entry and uncover a new role for inhibitory SMADs (I-SMADs) in viral pathogenesis.…”
mentioning
confidence: 99%
See 2 more Smart Citations